Finite difference code for velocity and surface traction of a Fluid between Two Eccentric Spheres - Wahab, M.Abdel (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The Numerical study of the flow of a fluid in the annular region between two eccentric sphere susing PHP Code is investigated. This flow is created by considering the inner sphere to rotate with angular velocity 1 ï— and the outer sphere rotate with angular velocity 2 ï— about the axis passing through their centers, the z-axis, using the three dimensional Bispherical coordinates (ï¡,ï¢ ,ïª) .The velocity field of fluid is determined by solving equation of motion using PHP Code at different cases of angular velocities of inner and outer sphere. Also Finite difference code is used to calculate surface tractions at outer sphere.